When Credibility Meets Narrative: Dual Mechanisms Driving Consumer Brand Engagement - Rahmawati; Primanto, Alfian Budi; Arifin, Rois; Mohd Salleh, Muhammad Zulfaris (Universitas Airlangga, 2025)
Objective: Utilizing Source Credibility Theory and Narrative Persuasion Theory, this study develops a framework that positions influencer credibility and storytelling as dual antecedents of positive emotion and consumer trust toward consumer brand engagement. Homophily is introduced as a boundary condition that strengthens or weakens the pathways from emotion and trust to engagement. Design/Methods/Approach: A quantitative research design was employed using an online survey distributed to active social media users who follow brand-endorsing influencers. 416 respondents meet with criteria and PLS-SEM technique is applied for data analysis Findings: Results reveal that influencer credibility enhances consumer brand engagement through the mediation of positive emotion, whereas storytelling influences consumer brand engagement via consumer trust. Furthermore, homophily significantly strengthens the effect of positive emotion on engagement but has a weaker moderating influence on the trust–engagement relationship. Originality/Value: This study contributes to the influencer marketing and advertising literature by integrating affective and cognitive perspectives into a unified engagement framework. It extends existing theories by demonstrating how credibility and storytelling operate through parallel emotional and trust-based processes, and by identifying homophily as a boundary condition that differentiates emotional from cognitive persuasion. Practical/Policy implication: Given the results, managers seeking to create successful influencer-driven marketing campaigns are advised to collaborate with credible influencers who can communicate brand messages through authentic storytelling formats. Campaigns should also target audiences with shared lifestyles and values to enhance emotional resonance and trust formation. These strategies will optimize brand engagement and strengthen long-term consumer relationships in social media advertising.